Exploring International Service-Learning Boundaries - Annie Wendel (The University of Alabama, 2022)
A review of the book: Patrick M. Green and Mathew Johnson (2014). Crossing Boundaries: Tension and Transformation in International Service-Learning. Sterling, Virginia: Stylus Publishing, LLC. 294 pages. ISBN: 978-1579226206